Yield Response and Nutrient use Efficiencies of Maize (Zea mays L.) As Determined through Nutrient Omission trials in Jimma Zone, Southwestern Ethiopia - Getinet, Habetamu; G.Selassie, Yihenew; Balemi, Tesfaye (Journal of Agriculture and Environmental Sciences, 2022)
Appropriate fertilization based on actual limiting nutrients and crop requirements is economic and judicious for sustainable crop production. A field experiment was conducted to identify yield-limiting nutrients, to determine yield response, nutrient uptake and use efficiencies of maize (Zea mays L.) through nutrient omission technique in the Nitisols of Omo Nada District Southwestern Ethiopia for one cropping season (2019/20). The experiment was laid out in Randomized Complete Block Design with four replications. The treatments were control, NP, PKS (-N), NKS (-P), NPS (-K), NPK (-S), NPKS, NPKSZn (-B), NPKSB (-Zn) and NPKSZnB. One composite soil sample was collected from an experimental plot at a depth of 0-20cm before treatment application and analyzed to estimate the inherent N, P, K, S, Zn and B supplying capacity of the soil. Grain and straw samples were collected to determine N, P, K, S, Zn and B contents. Maize yield and yield components, nutrient uptake and agronomic efficiencies of maize were subjected to ANOVA using SAS 9.3 software. The LSD test was used to separate means at a 5% level of significance. The results of soil showed moderately acidic, sandy clay loam texture, low total N, available P and medium in K, S, Zn, B, OC, OM and CEC. Grain yield and yield components, nutrient uptake and agronomic efficiency of each nutrient were significantly affected due to nutrient omitting. Accordingly, the highest grain yield response of maize (5909.1kg ha-1) was obtained from N fertilized plots indicating N was the most yield-limiting nutrient. Owing to the magnificent yield response to N fertilizer in the current study, proper management of N is very essential for the intensification of maize productivity. The maximum total nutrient uptake of N (87.38), P (40.40), K (114.95), S (22.22), Zn (2.67), B (0.28) and agronomic efficiencies of N (55.6), P (166.9), K (166.9), S (333.7), and Zn (1359.8) was obtained from integrated use macronutrients (NPKS) with Zn.